The Effect of Catfish Meat Substitution on the Physical and Organoleptick Quality Of Meatbals with Rejected laying HenMeat - Hafid, Harapin; St Nur Anggraeni S; Pagala, Amrullah (Talenta Publisher, 2023)
Consumer pleasure for meatballs needs to be innovated with various ingredients including catfish meat and chicken meat. This study aims to determine the effect of catfish substitution on the physical and sensory quality of rejected laying hen meatballs. This study used an experimental method which is a completely randomized design (CRD) with 5 treatments and 5 repetitions. The treatment used was as follows, (P0) 100% meat of rejected layers, (P1) 80% meat of rejected layers: 20% catfish, (P2) 70% meat of rejected layers: 30% catfish, (P3) 60% meat of rejected layers: 40% catfish, (P4) 50% meat of rejected layers: 50% catfish. The parameters measured in this study were the organoleptic test of meatballs of rejected laying hen meat which had no significant effect (P>0.05) on all variables including color, shape, aroma, texture, taste and general acceptance of meatballs, aroma, tenderness, taste, texture and color of meatballs